Gestión de documentos y su incidencia en el almacenaje de la correspondencia escrita del Agro Servicio Fer – Plant en el cantón Simón Bolívar del año 2022 - Perez Manzaba, Darlin Hannibal (2022)
This research work has as a fundamental part to know what is the existing predominance of document management and its impact on the storage of written correspondence; Thanks to the support and pertinent expertise of the Fer-Plant Agro Service with jurisdiction in the Simón Bolívar canton, it has been possible to carry out a vast examination and study. To carry out this, it has been fundamental to show conformity to the specific concepts of the topics that interfere in this investigation and then move on to the conceptualization of the techniques that will be put into effect; Those typologies are: field research that, together with observation, can be understood in the first instances of the problem that is occurring, therefore the quantitative procedure was put into effect that, as it is already known, this tool helps us to tabulate, graph and perform a much simpler analysis and to finish this part is the analytical method which allows you to easily interpret each variable of the problem. As a last part is the answer to the results achieved in which the reasons why it could be said hypothetically that there are problems in the institution are detailed. To finish this research work, it was necessary to give some recommendations that will be very useful for the members of the company, be these directors even for the same assistants, if they considered it pertinent for the use of said recommendations for the development of Your activities.